Education in the face of digital media: a brief look at intellectual development during the teaching-learning process - Ananias Junior, Luiz Francisco [UNESP]; Morais, Osvando Jose de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
Digital media has been impacting society in many areas, including economic, health, security and, not unlike the others, education. With the popularization of high-speed mobile internet services, smartphones followed suit and represented the inclusion of thousands of people in the world wide web. Given this reality, these tools brought with them an explosion in the use of these devices by children and young people. Therefore, this article seeks to understand the paradigm of intellectual development of this group based on the teaching-learning process influenced by these media through a brief bibliographic review and analysis of data made available by institutions on the subject.
Keywords: Education; mediatization; digital media; intellectual development; teaching- learning